2021
DOI: 10.1016/j.ijid.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial analysis of COVID-19 transmission in China and its influencing factors

Abstract: Objectives The purpose of this study was to explore the temporal and spatial characteristics of COVID-19 transmission and its influencing factors in China from January to October 2020. Methods About 81,000 COVID-19 confirmed case data, Baidu migration index data, air pollutants, meteorological data, and government response strictness index data were collected from 31 provincial-level regions (excluding Hong Kong, Macao, and Taiwan) and 337 prefecture-level cities. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…This was because the high-risk and medium-risk areas were the first to be affected by the pandemic ( Li et al, 2021 ) and the continuous fermentation of the online negative sentiment caused a public panic, which led to panic buying behaviors. However, as there were no confirmed COVID-19 cases in the low-risk areas in the early pandemic stages ( Wang et al, 2021 ), the public was less susceptible to the online negative sentiment and tended to follow their normal purchasing behaviors. As the pandemic became more serious, the low-risk area public began to panic, fearing there could be shortage of supplies in the future, which resulted in bulk purchasing behaviors and a continual rise in the agricultural product prices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was because the high-risk and medium-risk areas were the first to be affected by the pandemic ( Li et al, 2021 ) and the continuous fermentation of the online negative sentiment caused a public panic, which led to panic buying behaviors. However, as there were no confirmed COVID-19 cases in the low-risk areas in the early pandemic stages ( Wang et al, 2021 ), the public was less susceptible to the online negative sentiment and tended to follow their normal purchasing behaviors. As the pandemic became more serious, the low-risk area public began to panic, fearing there could be shortage of supplies in the future, which resulted in bulk purchasing behaviors and a continual rise in the agricultural product prices.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the public in the medium-risk areas were more likely to be affected by the public online negative sentiment and to adopt irrational panic buying behaviors, which in turn resulted in a sustained and greater impact on prices. As the low-risk areas were less affected by the pandemic, the public was less affected by the online negative sentiments ( Wang et al, 2021 ), which meant that the agricultural product price responses to the public online negative sentiments were lower than in the medium-risk areas. Life cycle impulse responses …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But the other studies also showed similar results For instance, Han et al [ 20 ] have found the trend change characteristics of Moran’s I index slightly raised from 0.007 to 0.013 in Beijing, China. Another study by Wang et al [ 21 ] also revealed the trend of Moran’s I index values in 31 provincial-level areas of China slightly increased from 0.01 to 0.17. Based on this comparison, we estimated that the average of the Moran’s I index of the number of COVID-19 cases just slightly increased all over the world.…”
Section: Discussionmentioning
confidence: 93%
“…The inquiry frequency and concerning problems from the users have been well documented by internet platforms and their demographic data. Using data from these internet platforms, infodemiology research has been successfully practiced in reporting disease incidence [ 7 , 8 ], surveilling pandemic outbreaks [ 9 , 10 ], and analyzing other public health events and related public awareness [ 11 , 12 ]. Previously, public interest and the change over time of the search volume in sexual dysfunction were analyzed [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%